Pemberdayaan Kelompok Tenun Ikat Tonu Wujo Yang Berbasis pada Kearifan Lokal dan Partisipasi Masyarakat di Desa Tiwatobi Kecamatan Ile Mandiri (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The Kani Wujo Ikat Weaving Group in Tiwatobi Village, Ile Mandiri District is a representation of local wisdom that plays an important role in maintaining cultural identity and supporting the local community's economy. However, the group's development faces challenges in the form of limited product innovation, narrow market access, and lack of managerial training that meets local needs. This study aims to examine an empowerment model based on local wisdom and community participation to strengthen the sustainability of the Kani Wujo Ikat Weaving Group. The type of research used is qualitative descriptive with a case study approach. Data was collected through in-depth interview techniques, participatory observation, and documentation studies, involving weavers, traditional leaders, and village officials as the main informants. Data analysis is carried out interactively through the process of data reduction, data presentation, and conclusion drawn, according to the Miles and Huberman analysis model. The results of the study show that group empowerment based on local wisdom and community participation encourages the maintenance of cultural values in weaving production, strengthens social solidarity, and increases adaptation to information technology in marketing. However, there is also a need to improve design innovation, expand market access, and strengthen the capacity of group financial literacy. In conclusion, approaches based on local wisdom and community participation are effective in maintaining the sustainability of traditional businesses and strengthening the economic resilience of communities. The suggestion for further research is to expand the focus on developing cultural-based business model adaptation strategies in the midst of global market dynamics and to quantitatively assess the economic impact of community empowerment based on local wisdom.